Fluidic Processing of High‐Performance ZIF‐8 Membranes on Polymeric Hollow Fibers: Mechanistic Insights and Microstructure Control. (1st June 2016) - Eum, Kiwon; Rownaghi, Ali; Choi, Dalsu; Bhave, Ramesh R.; Jones, Christopher W.; Nair, Sankar
Abstract : Recently, a methodology for fabricating polycrystalline metal‐organic framework (MOF) membranes has been introduced – referred to as interfacial microfluidic membrane processing – which allows parallelizable fabrication of MOF membranes inside polymeric hollow fibers of microscopic diameter. Such hollow fiber membranes, when bundled together into modules, are an attractive way to scale molecular sieving membranes. The understanding and engineering of fluidic processing techniques for MOF membrane fabrication are in their infancy. Here, a detailed mechanistic understanding of MOF (ZIF‐8) membrane growth under microfluidic conditions in polyamide‐imide hollow fibers is reported, without any intermediate steps (such as seeding or surface modification) or post‐synthesis treatments. A key finding is that interfacial membrane formation in the hollow fiber occurs via an initial formation of two distinct layers and the subsequent rearrangement into a single layer. This understanding is used to show how nonisothermal processing allows fabrication of thinner (5 μm) ZIF‐8 films for higher throughput, and furthermore how engineering the polymeric hollow fiber support microstructure allows control of defects in the ZIF‐8 membranes. The performance of these engineered ZIF‐8 membranes is then characterized, which have H2 /C3 H8 and C3 H6 /C3 H8 mixture separation factors as high as 2018 and 65, respectively, and C3 H6 permeances as high as 66 GPU. Abstract : Formation of metal‐organic framework membranes in microscopic hollow fibers proceeds via specific mechanisms that combine interfacial reaction and crystallization with reactant transport under microfluidic conditions. It is shown that these mechanisms can be understood and then controlled by approaches such as nonisothermal processing and modification of fiber microstructure, leading to high‐performance ZIF‐8 membranes for olefin and hydrogen production.